Strategi Pengelolaan Taman Wisata Alam Gunung Meja melalui Penataan Kawasan - Daniel Leonard; Anton S. Sinery; Jacob Manusawai (Program Pascasarjana Universitas Papua, 2020)
The purpose of this research is to formulate management strategies related to the condition and potential of the park. The results showed that land cover of Gunung Meja natural tourism park dominated by natural forest (77.5%), followed by plantations forest (11.7%), the former garden area (5.6%), gardens (3.4%) and open land, electricity network, tower and street with percent smaller extent. Potential natural forest vegetation is very high, includes 159 species of trees (186 individuals/ha, high diversity indeck), 149 species of poles (867 individuals / ha, medium diversity indeck), 164 species of saplings (3,904 individuals / ha, medium diversity indeck) and 177 species of seedlings (32,300 individuals / ha, medium diversity indeck) with the total of species is 223, as well as forest vegetation plants, medicinal plants and farm / plantation vegetation. The diversity of wildlife species include 15 species of mammals (2 species protected), 35 species of birds (12 species protected), 21 other species (8 lizards, 3 amphibia, 9 snakes and 1 turtles) and 14 species of insects (1 species protected). Potential support includes Japanese monument, caves, water and social communities. Utilization of the region has not done so well that affect the area as a result of the existence of agricultural activities, logging and utilities. Referral management includes policies (policies that embody accommodate all interests through the zoning system by protected zone, farm exploit zone and buffer zone).